Menahem Pressler : Artistry in Piano Teaching - Brown, William Paul, 1947- (Book collections on Project MUSE., 2009)
As soloist, master class teacher, and pianist of the world-renowned Beaux Arts Trio, Menahem Pressler can boast of four Grammy nominations, three honorary doctorates, more than 80 recordings, and lifetime achievement awards presented by France, Germany, and Israel. Former Pressler student William Brown traces the master's pianistic development through Rudiakov, Kestenberg, Vengerova, Casadesus, Petri, and Steuermann, blending techniques and traditions derived from Beethoven, Chopin, Liszt, and J.S. Bach. Brown presents Pressler's approach to performance and teaching, including techn.